AN INVESTIGATION INTO METAPHORS USED IN INAUGURAL ADDRESSES MADE BY THE PRESIDENTS OF THE UNITED STATES - Ph.D. Ngũ Thiện Hùng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at: - Examining metaphorical expressions in inauguration speeches made by presidents of the United States. - Helping the readers to be aware more about the role of metaphor in inaugural speeches.